Facile synthesis of a glass film containing Ca2CuO3 micro-crystals and exhibiting a third-order non-linear property. Issue 14 (1st November 2016) - Yin, Congfei; Xiang, Weidong; Hu, Guangcai; Hu, Xie; Fan, Weibin; Chen, Xipeng; Xiang, Run; Liang, Xiaojuan
Abstract: A two-step synthetic method was used to obtain a Pb glass film containing micro-crystalline Ca2 CuO3 particles on a K9 glass substrate. The Ca2 CuO3 micro-crystals were prepared for the first time by a high-temperature solid state method. The synthesized films were obtained on K9 glass substrates by screen-printing and co-sintering techniques, using Pb glass powder and Ca2 CuO3 micro-crystals as reagents under different sintering temperatures. Secondly, micro-crystalline Ca2 CuO3 Pb-glass films with different thickness were obtained by mechanical polishing for various times. The analysis of the surface structure, purity of the Ca2 CuO3 phase and confirmation of the Pb-glass components in the given composites were provided by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). The interactions between phonons and atoms of the micro-crystalline Ca2 CuO3 particles embedded in the Pb-glass matrix were characterized by means of Raman scattering spectra. Moreover, the nonlinear optical property of the film was detected by a top-hat Z-scan technique with a laser duration of 190 ns at 532 nm. The results showed that the film polished for 120 min exhibited a large third-order non-linear susceptibility χ (3) of 6.1×10 −12  esu, suggesting its potential application in all-optical switches and integrated electron devices.